Seroprevalence of bovine viral diarrhea virus infection and its associated risk factors in dairy cattle in and around Sebeta sub city, Ethiopia - Teferi Tura; Yobsan Tamiru; Chala Dima; Abebe Garoma; Abriham Kebede; Debela Abdeta (Scientific Reports)
Abstract Bovine viral diarrhea (BVD) is a highly infectious disease affecting cattle, leading to significant economic losses in many countries engaged in cattle production. From February 2022 to October 2022, a study was conducted to determine the seroprevalence and associated risk factors of Bovine Viral Diarrhea Virus (BVDV) in the Sebeta subcity area of Sheger city, Ethiopia. The study utilized a semi-structured questionnaire to gather information on herd management practices from dairy farm owners. Serum samples from 170 individual cattle across 34 herds were collected and tested for BVDV antibodies using the indirect enzyme-linked immunosorbent assay (ELISA). The prevalence of BVD antibodies at both the animal and herd levels was analyzed, and potential risk factors were identified using Chi-square analysis and logistic regression. The study found that 19.41% of individual cattle (33 out of 170) and 44.12% of herds were positive for BVDV antibodies. Multiple logistic regression analysis identified several significant risk factors associated with BVDV infection. Multiparous dairy cows were found to be 2.3 times more likely to be seropositive compared to primiparous and nulliparous cows. Crossbreed dairy cattle had double the odds of being seropositive compared to pure breeds. Additionally, cattle from larger herds were 5.01 times more likely to be seropositive than those from smaller herds. Farms that introduced new animals had triple the odds of seropositivity compared to those that did not. The study indicates a high exposure rate of cattle to BVDV infection in and around Sebeta sub-city. Further research is recommended to explore the molecular epidemiology of BVDV in the region.